Frequency Of Functional Outcome In Management Of Post Burn Neck Contractures - Sidra Memon; Mansoor Ali; Sadia Rsheed; Aisha Masroor Bhatti; Sameena Naz (Journal of Rawalpindi Medical College)
Objective: To determine the frequency of functional outcomes in managing post-burn neck contractures. Descriptive study. At the department of plastic surgery.